Seizing the teachable moment: extreme weather events as catalysts for climate change dialogue, learning, and action - Ettinger, JA (2023)
Researchers have long examined how extreme weather events affect climate-related attitudes, beliefs, and behaviours among the public, with mixed results. However, proactive communication strategies to engage diverse members of the public about climate change when extreme weather events occur are comparatively under-researched. Further research is needed on the best practices, dynamics, and effects of communicating links between climate change and extreme weather. This topic is particularly timely given the recent development of extreme event attribution (EEA) techniques that assess how climate change affects the frequency and/or intensity of specific extreme weather events.